Assessment of Dentists Attitudes, Knowledge, Practices, and Challenges in Utilizing Rubber Dams for Restorative and Endodontic Procedures: An Online Questionnaire Survey - Mohamed Hshad; Khaled Elhenshiri; Ahmed Nouha (AlQalam Journal of Medical and Applied Sciences, 2024)
Rubber dams are essential for dental procedures, ensuring isolation, patient safety, and better work efficiency for dentists. However, their use is often limited by challenges such as difficulty in application, time constraints, and inadequate training. This study aimed to assess the attitudes, knowledge, practices, and challenges to rubber dam use during among dentists in Tripoli, Libya. A cross-sectional online survey involving 165 dentists was conducted using a validated 26-item questionnaire. Data were analyzed using chi-square tests, with significance set at p <0.05. Results showed that 67.9% of dentists had access to rubber dams, but only 64.8% used them. Lack of training during undergraduate studies was reported by 61.2%, and 42.4% identified inadequate training as the main barrier. Significant association were found between rubber dam use and gender, place of work, prior training, and years of practice. Although dentists expressed positive attitudes toward rubber dam use, barriers such as insufficient training, radiographic procedures, and time constraints hindered regular application. Enhanced training programs could improve acceptance rates. الحاجز المطاطي ضرورية لإجراءات طب الأسنان، حيث تضمن العزل، وسلامة المريض، وكفاءة العمل الأفضل لطبيب الأسنان. ومع ذلك، فإن استخدامها غالبًا ما يقتصر على تحديات مثل صعوبة التطبيق، وقلة الوقت، وقلة التدريب المناسب. هدفت هذه الدراسة إلى تقييم مواقف و معرفة و ممارسات و تحديات استخدام سدادة المطاط أثناء عمليات الترميم و اللب بين أطباء الأسنان في طرابلس، ليبيا. تم إجراء دراسة استقصائية عبر الإنترنت شملت 165 طبيب أسنان باستخدام استبيان مدقق مكون من 26سؤال. تم تحليل البيانات باستخدام اختبارات مربع كاي، مع تحديد الدلالة الإحصائية عند 0.05> р . أظهرت النتائج أن 67.9٪ من أطباء الأسنان لديهم إمكانية الوصول إلى الحاجز المطاطي، لكن 64.8٪ فقط يستخدمونها. أفاد 61.2٪ بعدم وجود تدريب خلال الدراسات الجامعية، وذكر 42.4٪ أن التدريب غير الكافي هو العائق الرئيسي. تم العثور على ارتباطات كبيرة بين استخدام الحاجز المطاطي والجنس ومكان العمل والتدريب السابق و سنوات الممارسة. على الرغم من أن أطباء الأسنان أعربوا عن مواقف إيجابية تجاه استخدام الحاجز المطاطي، إلا أن العقبات مثل التدريب غير الكافي، والإجراءات الإشعاعية، وقلة الوقت تعيق التطبيق المنتظم. يمكن أن تؤدي برامج التدريب المحسّنة إلى تحسين معدلات القبول